Ultimate psychometric tests : over 1000 practical questions for verbal, numerical, diagrammatic and personality tests - Bryon, Mike. (London Kogan Page Limited, 2018)
"Are you faced with an upcoming psychometric test as part of a job application? Do you want to practise your technique and perfect your score? The best-selling Ultimate Psychometric Tests, now in its fourth edition, is the biggest book of its kind, containing over 1000 practice test questions of a multitude of different types of tests with accompanying answers and explanations. Providing sample questions from all the major types of test, including verbal reasoning, numerical reasoning, personality questionnaires, non-verbal and diagrammatic reasoning, new tests also now include spatial recognition and visual estimation, situational awareness tests as well as quantities and conversion tests. Ultimate Psychometric Tests also includes an overview of which companies employ which tests, including L'Oreal, Sony, HMV, Toyota and IKEA among others and it has plenty of advice on how to get test-wise and seriously improve scoring. The use of psychometric tests in job selection procedures is more prominent than ever and for unprepared candidates they represent a considerable challenge that can get in the way of them successfully landing a new job. This is your definitive guide to acing any type of psychometric testing you encounter as well as keeping your mind sharp and active."--Back cover.
Psychometric tests and questionnaires: what are they? -- How to pass psychometric tests and questionnaires -- Situational judgement and personality questionnaires -- Verbal reasoning -- Numerical reasoning -- Non-verbal reasoning, mechanical comprehension and data interpretation -- Answers and explanations.
Keywords: Employment tests; Employee selection; Psychological tests; PSYCHOLOGY -- Statistics; Employee selection; Employment tests; Psychological tests